Efeito da poda da haste e da população de plantas sobre a produção do tomateiro - Pelúzio de Campos , Joênes; Colombo Belford , Cristovam; Domingos Galvão , José; Rezende Fontes, Paulo Cezar (Revista Ceres, 2025)
Two experiments were carried out to evaluate the effect of tomato (Lycopersi- con sculentum Mill) stem pruning (after the 3’4, 5th ana 7th clusters, checked against an unpruned crop) and plant population (20,000, 30,000, and 40,000 plants/ha) on tomato yield of the Sao Sebastido cultivar.